2016
DOI: 10.1016/j.yfrne.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in drug addiction and response to exercise intervention: From human to animal studies

Abstract: Accumulated research supports the idea that exercise could be an option of potential prevention and treatment for drug addiction. During the past few years, there has been increased interest in investigating of sex differences in exercise and drug addiction. This demonstrates that sex-specific exercise intervention strategies may be important for preventing and treating drug addiction in men and women. However, little is known about how and why sex differences are found when doing exercise-induced intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 329 publications
4
49
1
Order By: Relevance
“…The present findings show the durability of the SACC treatment as a sustainable, nondrug reward to achieve voluntary abstinence from illicit drug use on a long-term basis in humans. However, while SACC was used in our monkey laboratory to achieve reduced drug intake (see reviews by Carroll and Lynch 2016, Carroll and Smethells 2016), a healthy nondrug reward, such social/community reinforcement (Higgins et al 2003, 2008), physical exercise (Bardo and Compton 2015; Zhou et al 2015; Rawson et al 2015), or an employment-based therapeutic workplace (e.g., Silverman et al 2002) are suitable nondrug alternatives for application to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings show the durability of the SACC treatment as a sustainable, nondrug reward to achieve voluntary abstinence from illicit drug use on a long-term basis in humans. However, while SACC was used in our monkey laboratory to achieve reduced drug intake (see reviews by Carroll and Lynch 2016, Carroll and Smethells 2016), a healthy nondrug reward, such social/community reinforcement (Higgins et al 2003, 2008), physical exercise (Bardo and Compton 2015; Zhou et al 2015; Rawson et al 2015), or an employment-based therapeutic workplace (e.g., Silverman et al 2002) are suitable nondrug alternatives for application to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous results have been more variable (for review see 11), a comparison of all available studies indicates that the occurrence of sex differences may depend on exercise access conditions. Specifically, studies investigating effects of contemporaneous, but non-concurrent exercise, generally report equal efficacy of exercise at reducing drug intake in males versus females (43,47); whereas, studies using concurrent access conditions generally report greater efficacy in females versus males (39,48).…”
Section: Overview Of Recent Findings In Male and Female Animalsmentioning
confidence: 97%
“…Results from preclinical studies have also shown that exercise can prevent the development of addiction-like behaviors, such escalation, or the progressive increase in drug use over time (9), indicating that exercise may not only prevent drug use initiation, but may also prevent the development of features of substance use disorder. Exercise has also been suggested as a sex-specific treatment for substance use disorder, and evidence for these effects was reviewed in Part II (10; also see 11). …”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in male and female laboratory animals with results showing that exercise during abstinence, such as voluntary running in a wheel or forced running on a treadmill, reduces drug withdrawal signs (34–40), including craving (4143), and prevents the development of incubation of drug-craving (4452), an animal model of relapse defined by a progressive increase in drug-craving over abstinence (53). Exercise has also been suggested as a sex-specific prevention for substance use disorder, and evidence for these effects was reviewed in Part I (54; also see 55). …”
Section: Introductionmentioning
confidence: 99%